Need for new reference curves for height. Issue 11 (November 1989) - Chinn, S; Price, C E; Rona, R J
Abstract : Data from the National Study for Health and Growth, on children aged from 4.0 to 12.0 years measured in 1972, 1985, and 1986 were used to assess whether new growth standards are required, and which subgroups of children might require separate standards. The change over this period, from just over half a centimetre in the youngest girls to over a centimetre in the oldest boys, warrants the use of revised reference curves, which are also needed for Afro-Caribbean children.